(untitled) (The Review of Diabetic Studies, 2024)
Community-acquired pneumonia (CAP) affects older adults more than other age groups. This speeds up the disease’s progression and makes it harder to treat with drugs. This is especially true for people who have long-term health problems like type 2 diabetes and chronic obstructive pulmonary disease (COPD). This review assembles the latest research on the etiology and management of severe community-acquired pneumonia (CAP). Focusing on antibiotics informed by guidelines and pragmatic clinical considerations. The empirical selection of antibiotics, combination therapy for severe disease, and the transition to oral step-down regimens following clinical stability are all highlighted. The significance of pharmacokinetic and pharmacodynamic parameters was discussed for the safety and efficacy of treatment in elderly patients. It is a encompassing renal function, glycemic control, and potential drug-drug interactions. The review stresses both antimicrobial stewardship and personalized, pharmacist-led treatments to improve outcomes. The data indicates that patient-centered, personalized medication is crucial for managing severe community-acquired pneumonia. Particularly in individuals with multiple comorbidities.